2021
DOI: 10.3758/s13414-020-02232-7
|View full text |Cite
|
Sign up to set email alerts
|

Phasic pupillary responses modulate object-based attentional prioritization

Abstract: Visual attention studies have demonstrated that the shape of space-based selection can be governed by salient object contours: when a portion of an enclosed space is cued, the selected region extends to the full enclosure. Although this form of object-based attention (OBA) is well established, one continuing investigation focuses on whether this selection is obligatory or under voluntary control. We attempt to dissociate between these alternatives by interrogating the locus coeruleus-norepinephrine (LC-NE) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…In a recent electroencephalography (EEG) study, Arjona, Escudero, and Gómez (2016) manipulated the validity of a spatial pre-cue that indicated one of two possible locations of an upcoming monaural auditory stimulus with 50%, 68%, or 86% accuracy. The authors found that the size of the cueing effect within behavioral measures (RT and proportion of incorrect responses) scaled with the validity of the pre-cue, consistent with other reports ( O'Bryan & Scolari, 2021 ; Riggio & Kirsner, 1997 ; Vossel, Geng, & Fink, 2014 ). A similar scaling effect has also been observed within FBA, albeit to a lesser extent ( Huang, Xue, Wang, Hu, Bu, & Chen, 2018 ; Stilwell, Bahle, & Vecera, 2019 ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a recent electroencephalography (EEG) study, Arjona, Escudero, and Gómez (2016) manipulated the validity of a spatial pre-cue that indicated one of two possible locations of an upcoming monaural auditory stimulus with 50%, 68%, or 86% accuracy. The authors found that the size of the cueing effect within behavioral measures (RT and proportion of incorrect responses) scaled with the validity of the pre-cue, consistent with other reports ( O'Bryan & Scolari, 2021 ; Riggio & Kirsner, 1997 ; Vossel, Geng, & Fink, 2014 ). A similar scaling effect has also been observed within FBA, albeit to a lesser extent ( Huang, Xue, Wang, Hu, Bu, & Chen, 2018 ; Stilwell, Bahle, & Vecera, 2019 ).…”
Section: Introductionsupporting
confidence: 81%
“…Combined with our previous work ( Liang & Scolari, 2020 ), this potentially suggests an all-or-nothing deployment of FBA: once FBA emerges, increasing cue validities may not alter its magnitude. This contrasts with several demonstrations in the SBA literature showing that the size of the effect scales with the reliability of a spatial cue ( O'Bryan & Scolari, 2021 ; Riggio & Kirsner, 1997 ; Vossel et al, 2014 ), perhaps serving as an additional indicator that SBA and FBA distinctly operate on sensory signals (e.g. Ni & Maunsell, 2019 ).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, Nah and Shomstein (2020) also manipulated the probability of the different target locations with the same paradigm and found that object-based effects were affected by cue–target contingencies, and could even be reversed if the uncued object is the most likely target location. O’Bryan and Scolari (2021) also demonstrated object-based effects that were contingent on the cue–target relationship. In their study, when the cue was highly predictive of target location no object-based effect was observed, but when the cue was only mildly predictive of target location (and invalid trials were more common) then an object-based effect emerged.…”
Section: Discussionmentioning
confidence: 93%
“…Locus coeruleus activity is tightly linked to attentional processes. High LC activity due to strong arousal drives attentional prioritization within objects ( O’Bryan and Scolari, 2021 ), selective attention ( Dahl et al, 2020 ), and focused attention ( Aston-Jones et al, 1999 ). In contrast, low LC activity might be relevant for high behavioral flexibility and a state in which attentional functions require a low basal state to prepare for increasing activation in situations demanding a specific task performance ( Aston-Jones et al, 1999 ).…”
Section: Locus Coeruleus Activity Causes Inattention In Deliriummentioning
confidence: 99%